2017
DOI: 10.5435/jaaos-d-16-00920
|View full text |Cite
|
Sign up to set email alerts
|

Complication Rates After Total Hip and Knee Arthroplasty in Patients With Hepatitis C Compared With Matched Control Patients

Abstract: Further research is needed to establish quantifiable associations between hepatitis C and postoperative complications among patients with the disease who undergo total joint arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…HCV has been previously recognized as a risk factor for prosthesis-related complications following elective arthroplasty. 18 Prior research has associated HCV infection with a greater risk of PJI, 11 , 31 mechanical complications, 8 , 38 and revision surgery 23 , 31 after both total knee arthroplasty and total hip arthroplasty. At 1- and 2 years postoperatively, HCV patients in this study exhibited significantly higher rates of revision TSA, PJI, dislocation, and other mechanical complications compared to matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…HCV has been previously recognized as a risk factor for prosthesis-related complications following elective arthroplasty. 18 Prior research has associated HCV infection with a greater risk of PJI, 11 , 31 mechanical complications, 8 , 38 and revision surgery 23 , 31 after both total knee arthroplasty and total hip arthroplasty. At 1- and 2 years postoperatively, HCV patients in this study exhibited significantly higher rates of revision TSA, PJI, dislocation, and other mechanical complications compared to matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…There are mixed reports regarding the outcomes of THA among patients with hepatitis C. In a mid-term follow-up study, patients with hepatitis C were found to have similarly good implant survivorship and clinical outcomes after THA compared with matched controls 31 . Cancienne et al, however, showed that patients with hepatitis C had significantly higher risk of infection, aseptic revision surgery, medical complications, and blood transfusions compared with a matched cohort followed for up to 8 years 32 .…”
Section: Patient Factors In Relation To Outcomes Medical Comorbiditiesmentioning
confidence: 99%
“…Consequently, a study conducted by Cancienne et al. determined that HCV patients who did not receive treatment prior to total knee arthroplasty had higher rates of both infection and aseptic revision 3 months following surgery, which renewed interest in optimizing this high-risk cohort prior to TJA [ 13 ].…”
Section: Introductionmentioning
confidence: 99%